Thermal crumpling of perforated two-dimensional sheets - David Yllanes (Nature Portfolio, 2017)
Two-dimensional elastic membranes show great potential as functional materials, but how to engineer them with tunable mechanical properties remains challenging. Here, Yllanes et al. propose a method to induce the onset of crumpling transition in graphene-like sheets by simply altering their geometries.